Cultural and landscape zoning in the North-West Russia - Manakov, Andrei G.; Andreev, Alexander A. (Baltic Region, 2013)
This research was conducted in the framework of cultural geography — a relatively recent field of geography. This article considers the problems of geographical study of cultural landscapes of the North-West Russia, which includes Saint Petersburg, the Leningrad, Novgorod, Pskov, and Kaliningrad regions. This article sets out to develop and test the methodology for historical and cultural zoning at the mesogeographical level. The research and practical significance of the work lies in the identification of the features of formation of cultural landscapes in the North-West Russia, which can be used for the development of schemes of protection and rational management of territorial cultural and historical heritage. The authors rely on historical and cultural zoning as the basic geographical method of research on cultural landscapes. To this effect, the article offers a hierarchy of historical and cultural zones comparable to the zoning systems applied in physical, historical, and cultural geography. The major results of the research are the authors' taxonomy of historical and cultural complexes and the corresponding system of historical and cultural zoning of the North- West Russia presented on a sketch map. The article offers an exemplary description of historical and cultural provinces of the region. The contribution of the research to the Russian geography of culture is the authors' variant of taxonomy of historical and cultural complexes and the formulation of basic principles of historical and cultural zoning at different hierarchical levels. The research results can be applied, first of all, in the development of projects aimed at the protection and use of territorial cultural heritage in the framework of comprehensive schemes of territorial planning of the country's regions.